Structure and magnetic properties of a new iron(II) citrate coordination polymer. Issue 5 (26th February 2016) - Birsa Čelič, Tadeja; Jagličič, Zvonko; Lazar, Karoly; Zabukovec Logar, Nataša
Abstract : The new compound [Fe(H2 cit)(H2 O)] n (NICS‐2) is the first neutral ferrous citrate carboxylate that has been synthesized up to now. The iron citrate coordination polymer was hydrothermally synthesized and the structure was solved using single‐crystal X‐ray diffraction. It crystallizes in an orthorhombic space group P 21 21 21 (No. 19), with a = 5.9470 (4), b = 10.4021 (5), c = 13.5773 (7) Å, V = 839.91 (8) Å 3, Z = 4. Its structure consists of one‐dimensional chains of corner‐sharing Fe II O6 octahedra that are additionally cross‐linked with citrate ligands. Chains are additionally stabilized into a pseudo‐three‐dimensional structure by hydrogen bonds. The measurement of magnetic properties revealed that the magnetic moment is almost constant above 100 K (μeff = 5.1 µB ), but decreases rapidly below this temperature most probably due to the appearance of weak antiferromagnetic interactions between Fe atoms. Additionally, analysis of Mossbauer spectra confirmed the presence of divalent Fe atoms in the structure. Thermogravimetrical and X‐ray high‐temperature diffraction analyses showed the thermal stability of the material up to 548 K.